Project Tilurium - Coin Finds - Šeparović, Tomislav (2010)
During the decade long systematic archaeological research conducted on the site of Gardun (modern village of Trilj next to Sinj), the location of a former Roman military camp Tilurium, a total of 155 coins were discovered, of which 99 can be precisely identified and dated, and they are presented, analized and interpreted here.